Ferrocene‐substituted 3, 3′‐diindolylmethanes with improved anticancer activity. (6th March 2016) - Muenzner, Julienne K.; Ahmad, Aamir; Rothemund, Matthias; Schrüfer, Sebastian; Padhye, Subhash; Sarkar, Fazlul H.; Schobert, Rainer; Biersack, Bernhard
Abstract : A series of ferrocene‐substituted derivatives (2a, 2b, 2c, 2d, 2e, 2f, 2g ) of the known drug 3, 3′‐diindolylmethane (DIM ) were prepared and tested for their in vitro antitumor activity. The derivatives2a (featuring indole moiety), 2b (featuring 2‐methylindole moiety) and2f (featuring 5‐nitroindole moiety) were growth‐inhibiting in vitro at lower concentrations thanDIM in various tumor cells including pancreas cancer (BcPC‐3), three DIM‐resistant cancer cell lines (518 A2, KB‐V1/Vbl, HT‐29), triple‐negative breast cancer (MDA‐MB‐231) and prostate cancer (PC‐3). Derivatives2a, 2b and2f were the most active compounds of this series, qualifying as drug candidates for various cancer diseases. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : The 'nutraceutical' di(indol‐3‐yl)methane (DIM) was modified for improved antiproliferative effects in cancer cells by attachment of a ferrocene moiety at the methine bridge. The derivatives2a, 2b and2f were more active than DIM against breast, pancreas and prostate carcinoma cell lines, and also overcame the resistance to DIM of melanoma, cervix and colon cancer cell lines.